2019
DOI: 10.26858/ijole.v3i2.10657
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Conflicts of Needs in Designing Teaching English for Midwifery Students

Abstract: As an international lingua franca, English plays an important role for students of health for both academic and career success; however, it is often neglected in its planning and implementation. The present study aims at redesigning the teaching of English for midwifery students using an ESP approach by analyzing present situations (PSA), target situations (TSA), and learning situations (LSA) as the basis for designing English programs. The research was conducted at Midwifery Department, Polytechnic of Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…A number of research studies have reported that English at Higher Education becomes one of determining factors of ones' success in both academic and career (Antony, 2018;Daffa-Allah, 2012;Kaur, 2007;Lodhi, Shamim, Robab, Shahzad, & Ashraf, 2018); Poorhadi, 2017;Skelton & Whetstone, 2012;Woodrow, 2018). These studies are aligned with the previous studies conducted by Sujana, Fitriana & Syahrial (2016) and Sujana, Hanafi, Wilian, Syahrial, & Fitriana (2019). These authors found that English was perceived to have an important role to support the professional practices of those studying and working in medical fields.…”
Section: Introductionsupporting
confidence: 89%
“…A number of research studies have reported that English at Higher Education becomes one of determining factors of ones' success in both academic and career (Antony, 2018;Daffa-Allah, 2012;Kaur, 2007;Lodhi, Shamim, Robab, Shahzad, & Ashraf, 2018); Poorhadi, 2017;Skelton & Whetstone, 2012;Woodrow, 2018). These studies are aligned with the previous studies conducted by Sujana, Fitriana & Syahrial (2016) and Sujana, Hanafi, Wilian, Syahrial, & Fitriana (2019). These authors found that English was perceived to have an important role to support the professional practices of those studying and working in medical fields.…”
Section: Introductionsupporting
confidence: 89%
“…Dudley-evans et al (1998) define needs analysis as the process of establishing the what and how of how of a course. Needs analysis involves finding students' present situation (PSA) and target situation (TSA) before designing curriculum and syllabi (learning needs or LSA) (Sujana et al, 2019).…”
Section: Needs Analysismentioning
confidence: 99%
“…It is an invaluable language when it comes to connecting interactions between people all over the world. Sujana, Fitriana, and Syahrial (2016) argue that since English holds such a strong place, learning it is an essential need; otherwise, the people would face challenges if they are unable to communicate effectively in English. It is considered that the majority of people nowadays seek to be fluent in English since they want to have specific opportunities in a variety of ways (Abrejo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Finding a gap between the abilities of learners and the skills they need to have are the goals of needs analysis. Due to the complexities of the meanings of need, analyzing information and determining program decisions based on the results of need analysis is a challenging process (Sujana et al, 2019).…”
Section: Introductionmentioning
confidence: 99%